2022
DOI: 10.3389/fnut.2022.957932
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Honey as a Prebiotic Food to Re-engineer the Gut Microbiome Toward a Healthy State

Abstract: Honey has a long history of use for the treatment of digestive ailments. Certain honey types have well-established bioactive properties including antibacterial and anti-inflammatory activities. In addition, honey contains non-digestible carbohydrates in the form of oligosaccharides, and there is increasing evidence from in vitro, animal, and pilot human studies that some kinds of honey have prebiotic activity. Prebiotics are foods or compounds, such as non-digestible carbohydrates, that are used to promote spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 115 publications
0
18
0
1
Order By: Relevance
“…The dysbiosis in the gut mucosal environment leads to type I IFN enrichment in CD8 + T cells, resulting in increased anti-tumor immunity [52]. Honey has been shown to acquire protective prebiotic effects due to the presence of oligosaccharides and polyphenols as major constituents [53,54]. MH was shown to improve the growth of probiotic bacteria while inhibiting the growth of pathogens [55].…”
Section: Discussionmentioning
confidence: 99%
“…The dysbiosis in the gut mucosal environment leads to type I IFN enrichment in CD8 + T cells, resulting in increased anti-tumor immunity [52]. Honey has been shown to acquire protective prebiotic effects due to the presence of oligosaccharides and polyphenols as major constituents [53,54]. MH was shown to improve the growth of probiotic bacteria while inhibiting the growth of pathogens [55].…”
Section: Discussionmentioning
confidence: 99%
“…Honey has been used to treat digestive ailments since ancient times. Some honey types possess antibacterial and anti-inflammatory activities; furthermore, they can also promote wound healing [ 103 ]. Honey includes non-digestible oligosaccharides and studies have suggested that certain types of honey can act as a prebiotic by which to enhance the beneficial microbial population, including Bifidobacterium spp.…”
Section: Synbiotic Therapy To Alleviate Chemotherapy-associated Symptomsmentioning
confidence: 99%
“…and Lactobacillus spp., in the gut. This enhanced microbial population can help to relieve the symptoms of constipation and ulcerative colitis [ 103 , 104 , 105 , 106 , 107 ]. A Cochrane review of three studies investigating honey suggested that it was able to provide mild-to-moderate reduction in radiotherapy-induced oral mucositis [ 108 ].…”
Section: Synbiotic Therapy To Alleviate Chemotherapy-associated Symptomsmentioning
confidence: 99%
“…[48] Besides the antibacterial activity, honey may promote the repair of damaged intestinal mucosa, stimulate the growth of new tissues and work as an antiinflammatory agent. [40,[49][50]…”
Section: Antifungalmentioning
confidence: 99%